Blind equalization criteria for MIMO-FIR channels driven by colored signal - Bin GUO; Xue-mei BAI (Tongxin xuebao)
In view of the statistic characteristics of the colored source,the law presented by the second and the fourth order correlative statistics of this kind of source is analyzed.A blind equalization criterion for MIMO-FIR channel was proposed,and the blind equalization algorithm based on this criterion was also constructed.The validity of the proposed algorithm is demonstrated by computer simulations.